Soft Power and Foreign Policy Strategy Do Only Democracies Count? - Slavíková, Kamila; Zemanová, Štěpánka, 1975-; Halimzai, Pamir; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
A part of academic work inspired by Nye's concept of "soft power" has adopted his conceptualisation without much reservation, while another part has contested it. Some authors describe Nye's conceptualisation of power as biased towards democracies, or otherwise challenge the concept as category of analysis. On the case study of the partial democracy of Singapore, through analysis of official discourse, the thesis explores whether Singapore's government acknowledges the idea and if so, how it interprets it. Secondly, the thesis aims to provide more insight into the use of soft power as category of analysis with the help of the selected case study.
Vedoucí práce: Štěpánka Zemanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses